Optical and mechanical properties of translucent zirconium as an optimal restorative material in fixed prosthesis: A review of the literature - Escuza Gonzalez, Sergio (2022)
ntroduction: The main consequence of not treating tooth decay in time is the total or partial loss of the tooth. One of the alternatives to replace the lost tooth and return the functions is through fixed prostheses. Today there are 3 generations of yttrium-stabilized zirconium polycrystals (Y-TZP). Seeing that in the third Generation the yttrium content was increased to approximately 5% in moles (5Y), stabilizing the materials approximately 50% of cubic phase and 50% of tetragonal phase, thus giving a translucent zirconium (5Y) with a high aesthetics and greater naturalness to the dental crown. Objective: To identify the different optical and mechanical properties of translucent zirconium compared to other restorative materials used in fixed prostheses. Materials and methods: This narrative review evaluated 115 scientific articles from the Medline information sources (via PubMed), Science Direct, Scopus, SciELO and LILACS from the last 5 years, published in Spanish, Portuguese and English. We included 51 articles that met the selection criteria which were randomized clinical trials and observational studies, in vitro studies and in vivo studies that evaluated the optical and mechanical properties of translucent zirconium as an optimal restorative material in fixed prostheses. We excluded systematic reviews, case reports and editorials. Results: It was observed that zirconium being a relatively new material and in constant evolution has studies mostly in vitro, among which stand out those that speak both of the mechanical and optical properties that vary depending on the generation to which the material belongs, as well as the adhesiveness of the material which is for now not viable, therefore, it is essential that more studies be carried out on this material. Conclusions: We can mention that zirconium has evolved over time, providing better optical properties, but as a consequence it has been reducing flexural strength and fracture toughness. However, this material provides good biocompatibility with oral structures. On the other hand, translucent zirconium according to studies is a non-recordable material, so new methods are sought to improve its adhesion.